Ponovljivost testa aktivne gibljivosti vratne hrbtenice, izvedenega z inercijsko merilno enoto pri zdravih posameznikih - Lužnik, Izabela (Šport (Ljubljana), 2024)
Active range of motion can be measured with different measurement instruments for evaluating cervical spine function. The aim of the study was to determine intra-rater, test-retest and inter-rater reliability of active range of motion test of the cervical spine using an inertial measurement unit. Thirty-seven healthy adults participated in this study, who undertook the test on three occasions – the first and second assessments were performed within the same day, while the third assessment was performed 2-3 days later. The first assessment was conducted by rater A, while the second and third were conducted by rater B. During testing, the participants performed the following head and neck movements (6 repetitions): flexion, extension, left and right rotation, left and right lateral flexion. The intraclass correlation coefficients (ICC) obtained showed moderate to excellent intra-rater reliability for primary and associated movements (0,54-0,95). The results revealed that test-retest reliability was good to excellent for primary (0,76-0,93) and poor to good for associated movements (-0,23-0,80), while inter-rater reliability was moderate to excellent for primary (0,66-0,91) and poor to good for associated movements (-0,01-0,78). Measurements with inertial sensors have shown great potential for use in research, clinical and sports settings because they are practical, simple and relatively inexpensive, while providing quantitative assessment of cervical spine functionality through three-dimensional motion analysis.
Keywords: active range of motion; aktivna gibljivost; cervical spine; inerkcijska merilna enota; inertial sensors; ponovljivost merjenja; reliability; sport; šport; vratna hrbtenica